Resonance scattering of a transverse sound wave from a planar crystal defect - Kosevich, A.; Semagin, D. (Condensed Matter Physics, 1998)
Resonance scattering of a monochromatic transverse acoustic wave of the Rayleigh polarization from an isotop defect layer is considered. The phase velocity c of the incident wave along the defect plane is assumed to lie in the interval cl > c > ct . It is shown that the phenomena of the total reflection of the transverse wave from the thin plane defect and the total transition take place for the frequencies depending on the defect parameters. The former can always be observed for a heavy defect and never for a light one. The latter is possible for both light and heavy defects. Розглянуто резонансне розсiяння на ізотоп-дефектному шарі монохроматичної поперечної звукової хвилі релеївської поляризації. Фазова швидкість c падаючої хвилі вздовж дефектної площини за припущенням лежить в інтервалі ct < c < cl . Показано, що явища повного відбиття поперечної хвилі від тонкого плоского дефекту та повного проходження відбуваються при частотах, що залежать від параметрів дефекту. Перше завжди можна спостерігати для важких дефектів та ніколи для легких. Друге явище можливе як для важких, так і для легких дефектів.